Peace Around the World: American Foreign Policy Hits New Grounds - Grunwaldt, Bryce (My University, 2017)
The world was at war and needed to be rebuilt. The question was, how could the world go about rebuilding itself after such an event like after World War I? Could this sort of war be prevented in the future? Did the United States have similar solutions to the problem as other countries? President Wilson knew his answer, and his answer would set the grounds to the peace talks in Paris. With the use of newly made organizations like the Inquiry and then later on the American Commission to Negotiate Peace, the United States had a plan for a peaceful future, but the problem was that not everyone at the conference was on board.
USGZE AS333
Keywords: World War, 1914-1918 -- Diplomatic history; World War, 1914-1918